Compounding Benefits of Cholesterol-Lowering Therapy for the Reduction of Major Cardiovascular Events: Systematic Review and Meta-Analysis - Wang, Nelson; Woodward, Mark; Huffman, Mark D; Rodgers, Anthony (Circulation Cardiovascular quality and outcomes, 2022)
Mendelian randomization studies use genetic variants as natural experiments to provide evidence about causal relations between modifiable risk factors and disease. Recent Mendelian randomization studies suggest each mmol/L reduction in low-density lipoprotein cholesterol (LDL-C) sustained over a lifetime can reduce the risk of cardiovascular disease by more than half. However, these findings have not been replicated in randomized clinical trials, and the effect of treatment duration on the magnitude of risk reduction remains uncertain. The aim of this article was to evaluate the relationship between lipid-lowering drug exposure time and relative risk reduction of major cardiovascular events in randomized clinical trials. We conducted a systematic review and meta-analysis of randomized clinical trials of statins, ezetimibe, and proprotein convertase subtilisin/kexin type 9 inhibitors that report LDL-C levels and effect sizes for each year of follow-up. The primary end point was major vascular events, defined as the composite of cardiovascular death, myocardial infarction, stroke, and coronary revascularization. Hazard ratios during each year of follow-up were meta-analyzed using random-effects models. A total of 21 trials with 184 012 patients and an average mean follow-up of 4.4 years were included. Meta-regression showed there was greater relative risk reduction in major vascular events with increasing duration of treatment ( <0.001). For example, each mmol/L LDL-C lowered was associated with a relative risk reduction in major vascular events of 12% (95% CI, 8%-16%) for year 1, 20% (95% CI, 16%-24%) for year 3, 23% (95% CI, 18%-27%) for year 5, and 29% (95% CI, 14%-42%) for year 7. The benefits of LDL-C lowering do not seem to be fixed but increase steadily with longer durations of treatment. The results from short-term randomized trials are compatible with the very strong associations between LDL-C and cardiovascular events seen in Mendelian randomization studies.